Gedebage – Tasikmalaya Toll Gate Planning - Pamungkas, Triasco Handyan; Buana , Cahya (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
In general, transportation is the movement of people or objects from one place to another using a vehicle driven by humans or machines. Transportation is used to make it easier for humans to carry out their daily activities. A toll road is a road specifically for vehicles with two or more axles (cars, container trucks, buses, etc.) and aims to shorten the distance and travel time from one place to another. However, toll road often aims to shorten distances and time encounter obstacles. Obstacles occur because there are long queues at the toll gate. The method used in the Gedebage – Tasikmalaya toll gate planning was the First In First Out (FIFO) method, and the basic queue structure used Single Channel – Single Phase as the basic structure in the queuing process, which used 3 Automatic Toll Gate systems, On Board Unit (OBU), and Single Lane Free Flow using the FLO application. The planned gates included the Gedebage Gate with 7 substations, the Majalaya Gate with 6 substations, the Nagreg Gate with 4 substations, the North Garut Gate with 4 substations, the South Garut Gate with 4 substations, the Singaparna Gate with 4 substations, and the Tasikmalaya Gate with 4 substations.